O que é um pai?: articulações entre a noção de pai, em psicanálise, e o reconhecimento de paternidade no direito de família - NUNES, Isadora Elaine Sales (2018)
For Family Law, recognition of paternity occurs through the transmission of the father's surname in the child's certificate. Given the high number of children and adolescents without this surname - five million, according to the 2010 School Census -, the legal sphere has developed campaigns to encourage recognition of paternity, even if late, as in the case of the "Father being Present" campaign, inaugurated in 2010 by the National Council of Justice and the "Recognize is Love" in Maranhão. In pamphlets of the campaigns, the paternal surname inscription is usually related to a concrete acquisition of the father in the person's life or with the promise that, with recognition, there will be a bond of love between father and son. At the same time, the discourse that pervades such campaigns shows a prescriptive view of fatherhood. Thus, this work had as objective to discuss the notion of father in Psychoanalysis from the context of the legal campaigns of incentive to the recognition of paternity. We chose a theoretical exploratory research in which the texts of Freud and Lacan were taken as a basis, as well as the theorists of the Family Law who talk about filiation and the paternal recognition and the legislation in force on this subject. In Psychoanalysis, the notion of father articulates to the paternal and significant Father-Name function, shown by Lacan from his return to Freud. The paternal function is not restricted to the father being present or not concretely in the person's life, for even in his concrete absence, the father becomes present as a function. It is the father to appear for the son as the mother's prohibitor and institmer of a symbolic law, having effects in the constitution of the neurosis. Paternity involves unconscious questions about parenting, and it is not possible to think it in a prescribed way. The desire to have the father's last name, then absent, implies the updating of unconscious questions regarding the origin and place in the paternal family. In relation to the father, the possibility of transmitting his surname and calling someone as a son involves a place in the desire to give continuity to his lineage.